ohh okay so,
Lets assume Alex is A and Emma is E
so when we are told that Alex is 6 years older then Emma, we can say that emma (E) + 6 (because we're adding 6 to her age) equals the age of Alex (A), so this makes our statement true, because we are showing that Alex is 6 years older then Emma
5. A = 6 + E
Now for the second part of the question we are told, that if you add up Alex's (A) and Emma's (E) ages you get 32, so we know...
A + E = 32
so we have a set of simultaneous equations, so lets substitute, ( we can substitute these two equations to get rid of either A or E so that the question can now be solved). If you look at our first equation, its already in the form of A = ....... this is what we want because now we can put this ..... that A equals, into the A of our second equation to get rid of the A component in our second equation all together, so we get...
(6 + E {we put 6 + E instead of A}) + E = 32 (Putting the first equation into the second)
and now simplify
so 6 + 2E = 32
2E = 32 - 6
2E = 26
so E = 13
Lets put E back into any of the other ones to get A
so A = 6 + 13,
so A = 19
so emma is 13 and Alex is 19